Effect of Mineral Filler type on Strength of Roller Compacted Rubbercrete for Pavement Applications - Adamu, M. (Institute of Physics Publishing, 2017)
This paper investigated the possibility of using crumb rubber as partial replacement to fine aggregate in roller compacted concrete for pavement applications where fine aggregate was replaced with crumb rubber at 0, 10, 20 and 30 to produce roller compacted rubbercrete (RCR). In order to achieve a combined aggregate gradation similar to the one recommended by ACI 211.3R and US Army Corps of Engineers method, fly ash was used as mineral filler. Several trials were done to achieve the combined grading, and finally a combination of 55 fine aggregate, 40 coarse aggregate and 5 fly ash as mineral filler was used. Silica fume was then used as mineral filler instead of fly ash and the fresh density and compressive strength were compared. A target flexural strength of 4.5 MPa and the mix design was developed using the geotechnical concept according to ACI 211.3R/CRD-C161-92. The Results showed that fresh density and compressive strength decreases with increase in partial replacement of fine aggregate with crumb rubber. RCR containing silica fume showed lower fresh density and higher compressive strengths than that with fly ash. However, all the mixes achieved a strength higher than the design target strength at 28 days except for 30 crumb rubber containing fly ash mineral filler, while 10 crumb rubber achieved target strength even at 3 and 7 days for silica fume and fly ash. © Published under licence by IOP Publishing Ltd.